Estimation of Diosgenin by HPLC in a Dioscorea zingiberensis Collection from Different Local Markets in Middle and South Iraq - Al-Yassiry, Zahraa A.N.; jebor, Mohammed Abdullah; Al-Alwani, Basheer (International Journal of Scientific Research in Biological Sciences, 2024)
Diosgenin, a steroidal sapogenin, is found in significant quantities in some plant species, such as Dioscorea alata, Smilax China, and Trigonella foenum graecum. The bioactive phytochemical discussed in this context serves as a crucial precursor in the pharmaceutical sector for the synthesis of numerous steroidal medications. Additionally, it has demonstrated significant promise and garnered considerable attention for its potential therapeutic applications in addressing a range of disorders, including cancer, hypercholesterolemia, inflammation, and various infections. The objective of this research was to assess the diosgenin concentration in Dioscorea samples obtained from several local markets by the utilization of High Performance Liquid Chromatography (HPLC). The findings indicated that the content of Diosgenin was determined within the range assessed using the standard diosgenin. The utilization of high-performance liquid chromatography (HPLC) for the quantitative assessment of diosgenin has been determined to be a rapid, precise, straightforward, and cost-efficient alternative method for the examination of diosgenin.